Caspase-11-dependent pyroptosis of lung epithelial cells protects from melioidosis while caspase-1 mediates macrophage pyroptosis and production of IL-18. - Jinyong Wang; Manoranjan Sahoo; Louis Lantier; Jonathan Warawa; Hector Cordero; Kelly Deobald; Fabio Re (PLoS Pathogens, 2018)
Infection with Burkholderia pseudomallei or B. thailandensis triggers activation of the NLRP3 and NLRC4 inflammasomes leading to release of IL-1β and IL-18 and death of infected macrophages by pyroptosis, respectively. The non-canonical inflammasome composed of caspase-11 is also activated by these bacteria and provides protection through induction of pyroptosis. The recent generation of bona fide caspase-1-deficient mice allowed us to reexamine in a mouse model of pneumonic melioidosis the role of caspase-1 independently of caspase-11 (that was also absent in previously generated Casp1-/- mice). Mice lacking either caspase-1 or caspase-11 were significantly more susceptible than wild type mice to intranasal infection with B. thailandensis. Absence of caspase-1 completely abolished production of IL-1β and IL-18 as well as pyroptosis of infected macrophages. In contrast, in mice lacking caspase-11 IL-1β and IL-18 were produced at normal level and macrophages pyroptosis was only marginally affected. Adoptive transfer of bone marrow indicated that caspase-11 exerted its protective action both in myeloid cells and in radio-resistant cell types. B. thailandensis was shown to readily infect mouse lung epithelial cells triggering pyroptosis in a caspase-11-dependent way in vitro and in vivo. Importantly, we show that lung epithelial cells do not express inflammasomes components or caspase-1 suggesting that this cell type relies exclusively on caspase-11 for undergoing cell death in response to bacterial infection. Finally, we show that IL-18's protective action in melioidosis was completely dependent on its ability to induce IFNγ production. In turn, protection conferred by IFNγ against melioidosis was dependent on generation of ROS through the NADPH oxidase but independent of induction of caspase-11. Altogether, our results identify two non-redundant protective roles for caspase-1 and caspase-11 in melioidosis: Caspase-1 primarily controls pyroptosis of infected macrophages and production of IL-18. In contrast, caspase-11 mediates pyroptosis of infected lung epithelial cells.